Using vegetable extracts for help protect corn plants from pests Spodoptera frugiperda J. E. Smith In Tomohon City - Tairas, Tairas; Kaligis, James B.; Makal, Henny V. G. (Jurnal Agroekoteknologi Terapan, 2024)
Spodoptera frugiperda is a dangerous invasive pest because its life cycle is short and is often known by farmers as the brown armyworm pest on corn plants. Armyworms are included in the category of pests that are most difficult to control because the adults spread quickly and can fly long distances quickly. Armyworm control by farmers in Tomohon City generally uses synthetic pesticides. This activity aims to determine the use of the botanical insecticide soursop leaves, Pangi leaves, and citronella leaves against S. frugiperda pest attacks on corn plants. The research experiment was arranged in a randomized block design consisting of vegetable insecticide treatment from extracts of soursop leaves, Pangi leaves and citronella leaves treated with surfactant and a control. Each treatment was repeated 4 times. For one treatment, 20 corn plants are required. The application of vegetable insecticides is carried out 5 times with an application interval of once a week in the vegetative phase. The results of research on plant-based insecticides consisting of soursop leaf extract, Pangi leaf extract, and citronella extract are very effective in suppressing damage caused by Spodoptera frugiperda pests.  Fruit weight in soursop leaf extract weighed 314.59 grams per fruit, Pangi leaf extract weighed 338.75 grams per fruit, citronella extract weighed 345.00 grams per fruit and control weighed 230.14 grams per fruit Keywords: Botanical Insecticide, Spodoptera frugiperda   Abstrak Spodoptera frugiperda  merupakan salah satu hama invasif berbahaya karena siklus hidupnya pendek oleh petani sering dikenal sebagai hama ulat grayak coklat pada tanaman jagung. Ulat grayak termasuk dalam kategori hama yang paling susah dikendalikan karena imago cepat menyebar dan mampu terbang jarak jauh dalam waktu cepat.  Pengendalian ulat grayak yang dilakukan oleh petani di Kota Tomohon pada umumnya menggunakan pestisida sintetik.  Kegiatan ini bertujuan untuk mengetahui penggunaan insektisida nabati daun sirsak, daun pangi dan daun serai wangi terhadap serangan hama S. frugiperda pada tanaman jagung. Percobaan penelitian disusun dalam rancangan acak kelompok yang terdiri dari Perlakuan insektisida nabati ekstrak daun sirsak, daun pangi, dan daun serai wangi yang diberi surfaktan serta kontrol. Masing- masing perlakuan diulang sebanyak 4 kali. Untuk satu perlakuan diperlukan 20 Tanaman jagung. Aplikasi insektisida nabati dilakukan sebanyak 5 kali dengan interval waktu aplikasi seminggu sekali pada fase vegetatif. Hasil penelitian insektisida  nabati yang terdiri dari ekstrak daun sirsak, ekstrak daun pangi, dan ekstrak serai wangi sangat efektif untuk menekan kerusakan yang diakibatkan oleh Hama Spodoptera frugiperda.  Berat buah pada ekstrak daun sirsak memiliki berat 314,59 gram per buah, ekstrak daun pangi memiliki berat 338,75 gram per buah, ekstrak serai wangi memiliki berat 345,00 gram per buah dan control memiliki berat 230,14 gram per buah Kata Kunci : Insektisida nabati, Spodoptera frugiperda.